The structure of the crust, the uppermost mantle, and the mantle transition zone beneath Madagascar - Andriampenomanana Ny Ony, Elamahalala Fenitra Sy Tanjona (My University, 2017)
Since the arc assembly and continental collision of the East African Orogen some 640 million years ago, Madagascar has gone through several geodynamic and tectonic episodes that have formed and subsequently modified its lithosphere. This thesis aims to investigate the structure of the crust, the uppermost mantle, and the mantle transition zone beneath Madagascar to gain insights into the relationship between present-day lithosphere structure and tectonic evolution, and to evaluate candidate models for the origin of the Cenozoic intraplate volcanism. To address these issues, local, regional, and teleseismic events recorded by several temporary seismic networks; the MAdagascar-COmoros-MOzambique (MACOMO), the SEismological signatures in the Lithosphere/Asthenosphere system of SOuthern MAdagascar (SELASOMA), and the Réunion Hotspot and Upper Mantle – Réunions Unterer Mantel (RHUM-RUM) were used to complement the seismic events recorded by the permanent seismic stations in Madagascar. The different methods used and the primary results of this study are explained in each section of this thesis. In the first part of this thesis, crustal and uppermost mantle structure beneath Madagascar was studied by analyzing receiver functions using an H-κ stacking technique and a joint inversion with Rayleigh-wave phase-velocity measurements. Results reflect the eastward and northward progressive development of the western sedimentary basins of Madagascar. The thickness of the Malagasy crust ranges between 18 km and 46 km. The thinnest crust (18-36 km thick) is located beneath the western basins and it is due to the Mesozoic rifting of Madagascar from eastern Africa. The slight thinning of the crust (31-36 km thick) along the east coast may have been caused by crustal uplift and erosion when Madagascar moved over the Marion hotspot and India broke away from it. The parameters describing the crustal structure of Archean and Proterozoic terranes, including thickness, Poisson’s ratio, average shear-wave velocity, thickness of mafic lower crust, show little evidence of secular variation. Slow shear-wave velocity of the uppermost mantle (4.2-4.3 km/s) are observed beneath the northern tip, central part and southwestern region of the island, which encompass major Cenozoic volcanic provinces in Madagascar. The second part of the thesis describes a seismic tomography study that determines the lateral variation of Pn-wave velocity and anisotropy within the uppermost mantle beneath Madagascar. Results show an average uppermost mantle Pn-velocity of 8.1 km/s. However, zones of relatively low-Pn-velocity (~7.9 km/s) are found beneath the Cenozoic volcanic provinces in the northern, central, and southwestern region of the island. These low-Pn-velocity zones are attributed to thermal anomalies that are associated with upwelling of hot mantle materials that gave rise to the Cenozoic volcanism. The direction of Pn anisotropy shows a dominant NW-SE direction of fast-polarization in the northern region and around the Ranostara shear zone, in the south-central Madagascar. The anisotropy in the uppermost mantle beneath these regions aligns with the existing geological framework, e.g. volcanic complex and shear zones, and can be attributed to a fossil anisotropy. The Pn anisotropy in the southwestern region, around the Morondava basin, is E-W to NE-SW-oriented. It can be attributed either to the mantle flow from plate motion, the African superplume, or the Mesozoic rifting from Africa. Results from this study do not show any substantial evidence of the formation of a diffuse boundary of the Lwandle plate, cutting through the central region of Madagascar. Station static delays reflect the significant variation in the Moho depth beneath the island. In the third part of the thesis, the thickness of the mantle transition zone beneath Madagascar, which is sensitive to the surrounding temperature variation, has been estimated by stacking receiver functions. Single-station and common-conversionpoint stacking procedures show no detectable thinning of the mantle transition zone and thus no evidence for a thermal anomaly in the mantle under Madagascar that extends as deep as the mantle transition zone. Therefore, this study supports an upper mantle origin for the Cenozoic volcanism. However, the resolution of the study is not sufficient to rule out the presence of a narrow thermal anomaly as might arise from a plume tail. Overall, the findings in this research are broadly consistent with the crustal and upper mantle structure of Madagascar determined by previous studies, but provides significantly greater detail with regard to the crustal and uppermost mantle structure as more seismic stations were used.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy. October 2017.
Keywords: Geophysics--Madagascar; Earth (Planet)--Crust; Earth (Planet)-- Mantle; Lithosphere